Fisheries and conflict in the Zamboanga Peninsula 2019 - Ibáñez, Ana María (UK Data Service, 2020)
This survey is designed to capture in a systematic way the impact of armed group presence and governance arrangements on the conservation and sustainability of the fishing industry, and the outcomes these produce on local societies in terms of poverty, structural forms of inequality, and access to livelihoods. A representative sample of barangays from the Zamboanga Peninsula were selected, from which 1.500 households were randomly chosen to answer the household survey. The community survey was applied to community leaders in 60 sitios/puroks in the barangays where surveyed households live in order to obtain reliable and sensitive information on the context of the communities. The purpose of the survey is to capture the histories of local fishing communities on key topics: i) conflict dynamics; ii) production and organization of fishing activity; iii) social capital of households involved in fishing activities; iv) trends in conservation of maritime resources; and v) employment, poverty and inequality in local communities. The survey uses recall methods to constitute retrospective panel datasets. Sustainable fishing and the conservation of maritime resources requires regulation, but also efficient coordination and governance of common resources (fisheries and fish stocks) by local fishing communities. Armed conflict can significantly affect such capacity for collective action, with important consequences for the conservation of maritime resources and the livelihoods of local fishing communities. Yet, these effects have rarely been documented and analysed. This project will investigate the ways in which armed conflict and the presence of armed actors affects the capacity of fishing communities to manage and govern fishing activities, how this affects the conservation of maritime resources, and how this in turn affects the livelihoods of fishing communities, existing structural inequalities and their resilience to poverty, as these communities are particularly vulnerable to changes in production and access to environmental resources and climatic change. The project will focus on understanding the relationship between armed factions and fishing communities in the Southern shores of the island of Mindanao, the island of Basilan and the islands of the Sulu Archipelago in the Philippines. The region's armed conflict has induced a deep militarization of local economic, politics and societies but, to date, there is limited knowledge of how this has affected the fishing sector, the conservation of maritime resources, and how local fishing societies manage common fisheries, access sustainable livelihoods and build resilience to poverty. This project makes use of a multi-disciplinary, mixed methods approach to address this crucial gap in the literature. The juxtaposition of conflict and fisheries in the island of Mindanao is in addition a unique opportunity to understand the complex dynamics that emerges during conflict times and how governance structures of armed groups may cause lasting impacts on communities highly dependent on natural resources.